Lineshape of Magnetic Resonance and its Effects on Free Induction Decay and Steady-State Free Precession Signal Formation. (19th January 2020) - Ziener, C. H.; Uhrig, M.; Kampf, T.; Sturm, V. J. F.; Kurz, F. T.; Heiland, S.; Bendszus, M.; Pham, M.; Jakob, P. M.; Schlemmer, H.-P.; Buschle, L. R.
Abstract : Magnetic resonance imaging based on steady-state free precision (SSFP) sequences is a fast method to acquire T 1, T 2, and T 2 ∗ -weighted images. In inhomogeneous tissues such as lung tissue or blood vessel networks, however, microscopic field inhomogeneities cause a nonexponential free induction decay and a non-Lorentzian lineshape. In this work, the SSFP signal is analyzed for different prominent tissue models. Neglecting the effect of non-Lorentzian lineshapes can easily result in large errors of the determined relaxation times. Moreover, sequence parameters of SSFP measurements can be optimized for the nonexponential signal decay in many tissue structures.